Rancangan Media Audio Visual Tentang Perawatan Masa Nifas Sebagai Media Edukasi di Kota Tasikmalaya - Rismawati, Sariestya; Nurvita, Nita (HB PRESS, 2023)
The impact of the Covid-19 Pandemic that hit all over the world including Indonesia can also be seen in health services, one of which is the provision of health information about postpartum care. Lack of information about postpartum care is one of the reasons for the lack of postpartum visits. This has an indirect impact on the health quality of postpartum mothers, especially primiparous postpartum mothers. This condition requires attention, especially in increasing mother's knowledge about the importance of postpartum care. One thing that can be done is to provide health education with appropriate media. Audio-visual are considered to be usable because they are able to stimulate vision and attract more attention with attractive color and image compositions. The aim of this research is to analyse the eligibility of the audio visual media about postpartum care. The research method used research and development (R&D). This research has five stages from 10 stages: potential and problem analysis, data collection, product design, design validation, and design revision. Data validation media sources were the content expert and media expert. The subject of this research were 1 media expert ad 1 material expert. The data analysis used is quantitative analysis. The result of this research is audio visual media about postpartum care through 5 development design steps. The feasibility test for media experts obtained a score of 82.5% and material experts obtained a score of 97%. Conclusion,the audio visual about postpartum care is declared as very suitable and can be used to health promotion.